2016
DOI: 10.1111/jfb.13027
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and methyl mercury in fishes from Bacajá River (Brazilian Amazon): evidence for bioaccumulation and biomagnification

Abstract: This study assessed total mercury (THg) and methyl mercury (MeHg) concentrations, bioaccumulation and biomagnification of THg through the food web in fishes consumed by indigenous communities of Bacajá River, the largest tributary of the right bank of Xingu River. In total, 496 fish (22 species) were sampled. Nine species had THg concentrations above the limit recommended by the World Health Organisation (0·5 µg g(-1) wet mass), and one exceeded the recommended level for Hg in predatory fishes by Brazilian law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…They also developed an empirical method to estimate fish consumption from catch effort. The average daily fish consumption estimated for adult men was 216.75 g, and for women of childbearing age was 168.58 g. Considering that about 90–95% of total mercury species detected in fish samples is in the form of MeHg [ 47 , 48 , 49 ], we assume that all of the Hg detected in the fish samples is compounded by MeHg.…”
Section: Methodsmentioning
confidence: 99%
“…They also developed an empirical method to estimate fish consumption from catch effort. The average daily fish consumption estimated for adult men was 216.75 g, and for women of childbearing age was 168.58 g. Considering that about 90–95% of total mercury species detected in fish samples is in the form of MeHg [ 47 , 48 , 49 ], we assume that all of the Hg detected in the fish samples is compounded by MeHg.…”
Section: Methodsmentioning
confidence: 99%
“…The principal human exposure route to MeHg is the consumption of contaminated aquatic organisms, such as fish, shrimp, and crabs. To support this statement, numerous studies [31][32][33][34][35][36][37][38][39][40][41][42][43][44] carried out in the Amazon basin have revealed mercury concentrations in different fish species above the limits to commercialization established by FAO/WHO [45] (i.e., 0.5 µg MeHg/g for non-piscivorous fish and 1.0 µg MeHg/g for piscivorous fish). As a direct consequence of this fact, many scientific studies have been shown hair mercury concentrations from traditional Amazonian people that correspond to methylmercury intake in amounts several times greater than the safe limits recommended by FAO/WHO [25] and U.S.EPA [26], as we can see in some review papers [5,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…We chose hair samples as methylmercury exposure biomarkers because the principal source of mercury exposure in the studied population is the intake of mercury contaminated fish and from 90% to 95% of mercury forms observed in the fish muscle samples is methylmercury [ 58 , 59 , 60 ]. Besides that, almost all mercury present in hair samples is in the methylmercury form, allowing us to assume that all mercury detected in the hair is compounded by methylmercury [ 61 , 62 , 63 ].…”
Section: Methodsmentioning
confidence: 99%